Pattern of Visits to Older Family Physicians in Taiwan - Liu, Hao-Yen (Int J Environ Res Public Health, 2017)
Many family physicians still practice at an old age. Nevertheless, their practice patterns have scarcely been studied. To address this lack of research, the current study analyzed claims data for a total of 2,018,440 visits to 171 family physicians in 2011 sourced from Taiwan’s National Health Insurance Research Database. Family physicians aged 65 years and over had fewer patients (mean: 2330, standard deviation (SD): 2019) and visits (mean: 9220, SD: 8600) than younger physicians had. Furthermore, the average age of the patients who visited physicians aged 65 years and over was 51.9 (SD: 21.5) years, significantly higher than that of patients who visited younger physicians. However, the proportions of visits for upper respiratory tract infections, hypertension, diabetes mellitus, and dyslipidemia did not differ significantly among different age groups of physicians. In the future, the manpower planning of physicians should take into consideration the age structure and work profile of physicians.